The Strategi Peningkatan Keuntungan Bagi Pelaku Usaha Mikro Di Cibitung Kabupaten Bekasi - Uncok Cahyadi, Rony (LPPM Universitas Al Muslim, 2025)
The increasingly large and wide Micro, Small and Medium Enterprises (MSMEs) not only attract the interest of the public to become business actors. However, it is important for the government to take part in improving the economic aspects of MSMEs to encourage community income growth, especially in remote areas, to achieve prosperity of society fairly and equitably. Thus, an effort to encourage the progress of MSME businesses in order to achieve the expected targets is needed, emphasizing awareness of MSME actors themselves in running a business with the right strategy, simple, and easy to do. This is considered necessary, considering the large number of MSMEs, especially similar ones, resulting in increasingly high competition, and economic conditions that are currently declining, to manage and control their business as best as possible, without reducing the quantity and quality of products sold. This community service activity was carried out through the method of presentation and education on the importance of understanding strategies to increase profits in a simple and easy-to-understand manner in the form of presentations and discussions, as well as providing examples and practices regarding strategies in increasing the profits of Micro Business actors. The result of this activity is the right strategy in increasing profits to help MSME actors in their business sustainability and develop their businesses. Therefore, this activity should be carried out in a sustainable manner.